Low-Cost Forensics Reveal High Rates of Non-lethal Snaring and Shotgun Injuries in Zambia's Large Carnivores - White, Paula A.; Van Valkenburgh, Blaire (Frontiers in Conservation Science, 2022)
The impact of snaring and human-wildlife conflict (HWC) on large carnivore populations is of growing concern, and yet few empirical data are available. Mortality is the metric most often used, but non-lethal injuries that impact fitness are also important threats. However, because non-lethal injuries to wild carnivores are difficult to detect, they have received little study. Using straightforward forensic examination of the skulls of trophy-hunted lions and leopards from Luangwa Valley (LV) and Greater Kafue Ecosystem (GKE), Zambia, we identified non-lethal injuries consisting of snare damage to teeth and shotgun pellets in skulls. Wire snare entanglement can cause permanent, diagnostic damage to carnivore teeth when individuals bite and pull on the wire. Shotguns are used by poachers, as well as during HWCs to drive off carnivores perceived as threats. Carnivores struck by shotgun pellets can suffer non-lethal, but potentially toxic injuries such as pellets embedded in their skulls. Because poaching and HWC are generally more prevalent near human settlements, we predicted a higher incidence of anthropogenic injuries to carnivores in Luangwa where the human population is larger and more concentrated along protected area edges than Kafue. Contrary to expectation, anthropogenic injuries were more prevalent among lions and leopards in Kafue than Luangwa. Notably, definitive evidence of snare entanglement greatly surpassed previous estimates for these regions. Overall, 37% (41 in 112) of adult male lions (29% in Luangwa, 45% in Kafue) and 22% (10 in 45) of adult male leopards (17% in Luangwa, 26% in Kafue) examined had survived being snared at some point in their lifetime. Among adult male lions, 27% (30 in 112) had old shotgun pellet injuries to their skulls. Our procedure of forensic examination of carnivore skulls and teeth, some of which can be applied to live-captured animals, allows for improved detection of cryptic, non-lethal anthropogenic injuries. Further, our methods represent a consistent and economical way to track changes in the frequency of such injuries over time and between regions, thereby providing a direct measure of the effectiveness of conservation programs that seek to reduce poaching and HWC.